In-Filled La0.5Co4Sb12 Skutterudite System with High Thermoelectric Figure of Merit - Bashir, Mohamed Bashir Ali; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Miyazaki, Yuzuru; Shnawah, Dhafer Abdulameer; Shimada, Masanori; Salleh, Faiz; Mahmood, Mohamad Syafie; Salih, Ethar Yahya; Fitriani, Fitriani; Elsheikh, Mohamed Hamid (Springer, 2018)
The contribution of In addition to the La0.5Co4Sb12 skutterudite structure to improve its thermoelectric properties has been demonstrated. InxLa0.5Co4Sb12 (0 ≤ x ≤ 0.3) samples were prepared through mechanical alloying followed by spark plasma sintering. Characterization of the phase structure and morphology of the sintered InxLa0.5Co4Sb12 bulk samples was carried out using x-ray diffraction (XRD) analysis, scanning electron microscopy, and energy-dispersive x-ray spectroscopy. Rietveld analysis of the XRD spectra indicated that double filling at the 2a (000) interstitial site with La and In was successfully achieved, significantly improving the thermoelectric performance of the La0.5Co4Sb12 compound through simultaneous increase in the electrical conductivity and Seebeck coefficient. A maximum power factor of 3.39 × 10−3 W/m-K2 was recorded at 644 K for the In0.3La0.5Co4Sb12 sample, more than 96% of that of the La0.5Co4Sb12 sample. Double filling also effectively reduced the lattice thermal conductivity by about 46%, thus demonstrating that the overall improvement in ZT was primarily due to the reduced thermal conductivity. A maximum ZT value of 1.15 was achieved at 692 K for In0.3La0.5Co4Sb12.